Responsivity of Public Services in Indonesia during the Covid-19 Pandemic - Surya Arfan; Mayarni Mayarni; Mimin Sundari Nasution (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to determine the responsiveness of public services in Indonesia during the Covid-19 pandemic, this time digital bureaucracy is very much needed in every government agency in carrying out its duties and functions in order to accelerate the process of public services during the Covid-19 pandemic. Service standardization is the next most important thing to keep the bureaucracy running effectively, quickly and responsively in providing the best service to the community. This study chooses a qualitative research type with a literature review approach. The results of this study found that The Indonesian bureaucracy has not been able to respond to strategic problems in Indonesia quickly due to several obstacles to an apathetic bureaucratic culture, and the lack of participation of all parties in the public service process during the Covid-19 pandemic, there are still shortcomings in terms of speed, quality and community satisfaction. This is also influenced by overlapping policies that take a long time to implement.